LA RÈGLE DU JEU: VERLAN AS AN EXAMPLE OF ANTI-FAITHFULNESS - Gotowski, Megan (Linguistica Atlantica, 2019)
Verlan is a French language game characterized by the inversion of segments (for monosyllabic words) and syllables (for multisyllabic words). In this research, I explain why only certain patterns of reversal are possible. I provide an analysis of Verlan in terms anti-faithfulness (Alderete 2001). Furthermore, I argue that Verlan is best captured via a looping mechanism, viz. Raimy (1999), that is sensitive to the immediate successor relations found in the base. In Verlan, it is possible to (i) start the loop at a new point while respecting these relations, or (ii) reverse the original relations in the base—creating a mirror image—but it is not possible to do both.